Cuentas por cobrar del Benemérito Cuerpo de Bomberos del cantón Baba durante el periodo 2022-2023. - Suñiga Villavicencio, Angelica Anais (2024)
This study analyzes the accounts receivable management of the Baba Canton Fire Department during the period 2022-2023, identifying deficiencies in the recovery processes and proposing strategies aimed at optimizing the recovery of resources. The research aimed to examine the variation in accounts receivable, evaluate the internal and external factors that affect their recovery, and analyze the management process through internal control tools. The results reflect inefficiencies in collection management, a decrease in account turnover, and an increase in average agüe, evidencing the lack of structured policies and timely follow-up to delinquent taxpayers. The discussion of the findings revealed that factors such as the absence of flexible payment plans, incentive policies, and functional technological tools significantly limit the efficiency in account recovery. The conclusions highlight the need to implement a formal procedures manual, strengthen the use of automated technological systems, and train responsible personnel to ensure more effective management. Finally, it is recommended to design strategies that include incentives, regular monitoring and inter- institutional collaboration, with the purpose of improving liquidity and guaranteeing the financial sustainability of the Fire Department, thus facilitating its capacity to meet operational and service needs for the benefit of the community.